2014
DOI: 10.2337/diaspect.27.2.114
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Risk Perceptions in Older African Americans With Diabetes

Abstract: Objective. The purpose of this study is to describe the impact of depression on perceptions of risks to health, diabetes self-management practices, and glycemic control in older African Americans with type 2 diabetes. Methods. The authors analyzed data on depression, risk perceptions, diabetes self-management, and A1C in African Americans with type 2 diabetes. T-tests, χ2, and multivariate regression were used to analyze the data. Results. The sample included 177 African Americans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…The participants who reported more knowledge of DM and increased risk perceptions had at least a junior college education or were health care professionals ( n = 5). This trend is consistent with other research reports that people with less education are likely to report lower or higher severity of risk perceptions (Rovner et al, 2014).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The participants who reported more knowledge of DM and increased risk perceptions had at least a junior college education or were health care professionals ( n = 5). This trend is consistent with other research reports that people with less education are likely to report lower or higher severity of risk perceptions (Rovner et al, 2014).…”
Section: Discussionsupporting
confidence: 93%
“…This sense of powerlessness may be related to AA women’s cultural practices, experiencing stigma or discrimination, socio-economic status, historical experiences, and geographical locations. Similarly, other studies supported the possibility that limited knowledge or education might lead to both overestimation and underestimation of risks for disease and disease complications due to mistaken assessment of health status (Rovner et al, 2014).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Depressive symptoms can influence risk judgments. For example, African Americans with diabetes mellitus and clinical depression perceived themselves to be at higher risk of multiple health problems and adhered less to diabetes mellitus self‐management practices than those without depression . Although participants cited being old as one of the reasons for a positive response on both fall risk awareness questions, chronological age was not significantly associated with positive responses on either question.…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies have also shown that traumatized individuals who perceived the pandemic to be more severe and demonstrated psychological distress from COVID-19 were predicted to have poorer psychiatric outcomes across several countries (Li et al, 2020) [58,167,185]. Researchers believe that the combination of learned hopelessness and increased sensitivities to stress create poorer appraisals of taxing circumstances like fears involving infection and mortality [118,170,219]. These findings support the idea that individuals with histories of childhood trauma may be at higher risk for developing poorer psychological health during the COVID-19 pandemicespecially with regards to depression and other mood disorders.…”
Section: Trauma During Covid-19mentioning
confidence: 94%